Mixed Ligand Complexes of Mn(II), Pb(II) and Th(IV) with Adenosine Diphosphate and Nitrilotriacetate - Yadav, Sudha (Asian Journal of Chemistry, 2010)
A new method, paper electrophoresis, involving the use of ionophoretic technique, is described for the study of equilibria in mixed ligand system in solution. Migration of a metal ion spot (M), under an electric field, with complexant added in the background electrolyte at fixed pH 8.5, is studied. For the study of ternary complexes, the concentration of the primary ligand adenosine diphosphate (ADP) is kept constant while that of the secondary ligand nitrilotriacetate (NTA) is varied. Plot of -log [NTA] against mobility provided information about the mixed ligand complex to calculate the stability constants. As a prerequisite, binary equilibrium M-ADP and M-NTA have also been studied. The overall stability constants of M-ADP-NTA complexes have been found to be 109.04, 109.72 and 1010.49 for Mn(II), Pb(II) and Th(IV) complexes respectively at ionic strength μ = 0.1 and temp. 30° ± 0.1 °C.